PENGARUH ORIENTASI ALKES TERHADAP ADAPTASI ANAK USIA SEKOLAH YANG MENJALANI HOSPITALISASI PERTAMA - Sawitri, Ni Wayan (Coping: Community of Publishing in Nursing, 2015)
Hospitalization is a state of crisis in children when a child is ill and hospitalized. Children Adaptation of hospitalization consist of experience various aspects of hospital care including invasive procedures for diagnostic testing, pain, "creepy" and confusing hospital environment, the fear associated with age, hospital employees are not known, a lack of knowledge about the routines and treatment in the hospital. Orientation to new patients is an attempt to provide information/outreach to patients and families about all things related to hospital care. The purpose of this study was to determine the effect of medical devices orientation on adaptation of school age children undergoing first hospitalization in Sanglah Hospital. This research is a pre-experimental design with a static group comparison. The sample consisted of 22 pediatric patients were selected by quota sampling. Control group consisted of 11 children were observed and their adaptation measured by Adaptation Observation Sheet. 11 children who entered the intervention group were observed after given medical devices orientation first. Based on non-parametric test of Mann Whitney statistic with a significance value of p <0.05 significance value of 0.03 was obtained so that p = 0.03 <0.05. It can be concluded that there are significant effect of medical devices orientation on adaptation of school age children undergoing first hospitalization in Sanglah Hospital.
Keywords: Children; Hospitalization; Adaptation; Orientation; Medical Devices